To find the 7th term, all you have to do is plug it in the equation.
First n would equal 7 because we are looking for the 7th term.
Now, let's plug everything we know into the equation.
a7 = 2+5 * (7-1)
= 2 + 5 * 6
= 2 + 30
= 32
In conclusion, the 7th term would equal 32.
The value of 18x + 9∆x - 7 based on the limit given will be 18x - 7.
<h3>How to calculate the value?</h3>
From the information given, it should be noted that we simply want to calculate the value of x.
This will be:
18x + 9∆x - 7
It was stated that ∆x = 0
Therefore, we'll put this into the equation.
This will be:
18x + 9∆x - 7
= 18x + 9(0) - 7
= 18x -7
Learn more about limit on:
brainly.com/question/12383223
#SPJ1
Answer:
Kindly check explanation
Step-by-step explanation:
Given the following :
Group 1:
μ1 = 59.7
s1 = 2.8
n1 = sample size = 12
Group 2:
μ2 = 64.7
s2 = 8.3
n2 = sample size = 15
α = 0.1
Assume normal distribution and equ sample variance
A.)
Null and alternative hypothesis
Null : μ1 = μ2
Alternative : μ1 < μ2
B.)
USing the t test
Test statistic :
t = (m1 - m2) / S(√1/n1 + 1/n2)
S = √(((n1 - 1)s²1 + (n2 - 1)s²2) / (n1 + n2 - 2))
S = √(((12 - 1)2.8^2 + (15 - 1)8.3^2) / (12 + 15 - 2))
S = 6.4829005
t = (59.7 - 64.7) / 6.4829005(√1/12 + 1/15)
t = - 5 / 2.5108165
tstat = −1.991384
Decision rule :
If tstat < - tα, (n1+n2-2) ; reject the Null
tstat < t0.1,25
From t table :
-t0.1, 25 = - 1.3163
tstat = - 1.9913
-1.9913 < - 1.3163 ; Hence reject the Null
<span>-28x²-12x = -4x(7x+3) the first one is answer</span>
Answer:
y = -2x - 1
Step-by-step explanation:
y + 3 = -2 ( x - 1 )
y + 3 = -2x + 2
y = -2x - 1